How does digital transformation promote supply chain diversification? From the perspective of supply chain transaction costs - Cai, Junjie; Sharkawi, Ismawati; Taasim, Shairil Izwan (Elsevier Ltd, 2024)
Companies must implement digital transformation to achieve supply chain diversification with the current volatile economic conditions, which is crucial for their survival and as a fundamental measure to ensure industrial supply chain resilience and security. Based on A-listed companies, this paper systematically examines the impact of digital transformation on supply chain diversification, exploring the underlying mechanism of this effect from the transaction cost perspective. This paper reveals that digital transformation can significantly promote upstream suppliers, downstream customers, and the whole supply chain diversification. This impact operates mainly through the reduction effects of supply and demand coordination and inventory transportation costs. © 2024